IS-28 Small Animal Dental Anatomy and Pathology - Soenarti Daroendio (Hemera Zoa, 2018)
Teeth grow on a pair of upper and lower jaws. In the maxilla the incisors grow in the incisor bone, and the canines, pre molars and molars grow on the maxillary bone. In the lower jaw all tooth grow in the mandibular bone.To facilitate identification, the oral cavity is divided into 4 quadrants like the Triadan System modification. Consecutive quadran 1 to 4 are: right upper jaw, left upper jaw, left lower jaw and right lower jaw. And each tooth gets a 3 digit numbering identity: digit 1 is the number of the qudran where the tooth is growing, and 2 digits are then the number of each tooth starting from the sagittal piece to the two jaws to the right or left. For example: 101 is the identity for 1st incisors in the right upper jaw, 204 is the identity for the canines in the left upper jaw.